(3cJGH aj GdSjGSI hGdMces - (3GdhdjO Hf eMeO GdJOeQj, CHh GdYHGSs
(3ChdgG (B:s
(3Ef Chd eG GaJJM Hg GdcdGe aGdMeO ddg GdPi CfWb GdCdSfI HJMejOg LeYJ dc ai gPG GdcJGH ef eMGVQ cdGe GdHdZGA hfJGFL GacGQ GdMceGA s
(3BNQgG (B:s
(3hGdfbUGf ehcd HGdEfSGf hGdceGd dNGdb GdceGd aEf bUQJ ai ZGjg Ch GfbWYJ Ohf fgGjI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3RGhjI JJZdH GdeZQH(B) (35) s
Keywords: (3GdSjGSI hGdGLJeGYs